The Artwork as a Tool for Struggle: Inside and Outside Isola Art Center - Davide Da Pieve (piano b)
This study examines the experience of Isola Art Center, which originated in Milan in 2001 with Isola Art Project, as a paradigmatic case of socially engaged and participatory art. Departing from traditional models of exhibition and artistic reception, the project positions itself as an active tool of political and social resistance against urban gentrification. Through a dense network of relationships among artists, residents, urban planners, and institutions, Isola Art Center generated innovative practices and concepts—such as the dirty cube and fight-specific art—that call for a rethinking of conventional aesthetic and methodological frameworks within art historical analysis. In this context, the artwork becomes part of a broader cultural ecosystem, where relational dynamics, territorial conflicts, and forms of participation redefine both the role of the artist and the meaning of artistic creation. The study adopts a multidisciplinary and site-specific approach to explore the intersections between art and society, challenging the boundaries between the inside and outside of the art world and offering a reading that integrates aesthetics, politics, and practice.